Mala praxis y derecho penal costarricense: un énfasis en las cirugías estéticas - Bellanero Quesada, Adrian (2026)
Generally, when talking about a medical act, it is generally conceptualized from the point of view of curative medicine; and the same happens when defining the phases that are part of such act (diagnosis, treatment ...). This excludes satisfactive or voluntary medicine, which a branch of medicine that has proliferated with an exponential growth over recent years. This essay will address malpractice from the base of cosmetic surgery.